PEMBINAAN SEPAKBOLA KLUB GAPURA FOOTBALL CLUB KABUPATEN SAMBAS - Aril Aril; Ahmad Atiq; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe formulation of the research problem is 1) Is there vision and mission of the GAPURA Football Club,2) How is the management of the club, 3) How is the recruitment of GAPURA Football Club athletes, 4)How arethe facilities and infrastructure of the GAPURA Football Club, 5) What is the GAPURA FootballClub evaluation, 6) Wheter the coach has a training program, 7) Know the club’s funding. The purpose ofthis study was to determine: 1) The vision and mission of the GAPURA Football Club, 2) Knowing themanagement of the GAPURA Football Club, 3) Knowing recruitment of the club athletes, 4) Knowingfacilities and infrastructure, 5) knowing the evalution, 6) Knowing the training program, 7) Find out theclub funding. This research is a survey research. The sampling technique use the totaled sample technique,the number of sample is 41 people. Data collection techniques using questionaires. Data analysistechnique using descriptive quantitative. The results showed that 1) the vision and mission were said to be“very good” with percentage of 99%, 2) management was said to be “good” with a percentage of 89%, 3)athletes are said to be “very good” eith a percentage of 74%, 4) facilities and infrasteucture are said to be“good enough” with a percentage 0f 74%, 5) evalution is said to be “very good” with a percentage of97%, 6) the training program is said to be “very good” with a percentage of 98%, 7) funding is said to bhe“low” with a percentage of 48%. The results obtained from this study show that the construction of theGAPURA Football Club in Sambas regency is said to be “good” with a percentage of 88%.Keywords: GAPURA Football Club Coaching